CROSS‐BORDER BANKING, EXTERNALITIES AND SOVEREIGN DISTRESS: DOES THE EURO NEED A COMMON BANKING AUTHORITY?1. (4th April 2014) - Erce, Aitor
ABSTRACT This paper analyses the role of linkages between cross‐border banks and sovereigns in the spread of crises. After discussing evidence from past crises, I focus on the Euro Area. Banks from the Euro‐core played a key role in shedding the seeds for the transition from the US mortgage crisis to the Euro Area crisis. While national authorities supported their damaged banks, the Euro‐system's infrastructure allowed Euro‐core banks to undo intra‐area exposures with minor disruptions. Although this helped stabilize peripheral asset markets, the extent to which public funding replaced private one implied less macroeconomic correction and the current fiscal woes. The combination of cross‐border banking and national resolution schemes creates an externality on sovereigns, who are forced to contain the effects stemming from the balance sheet management of cross‐border banks. Weak public finances can easily push a banking crisis into a fiscal one. This negative externality is reinforced by Central Banks' mandate that limits fiscal cooperation. In the context of the Euro Area, to limit this problem, the Union should equip itself with a common bank resolution authority, which delinks banks and sovereigns. In addition, to limit the externality, macro‐prudential policy could set contributions for cross‐border operators in order to pre‐fund future bank rescues. Copyright © 2014 John Wiley & Sons, Ltd.